Perguruan Pencak Silat Alang Bangkeh Pauh V: Suatu Tinjauan Historis 1981-2018 - Feri Fanando Saputra; Abdul Salam (Jurnal Kronologi, 2020)
This Research explains about Alang Bangkeh Pauh V College of Pencak Silat in 1981-2018. This study uses a qualitative method of the processs: Heuristics (data colllection), then proceed with the process of source criticsm and interpretation of data, the final stage of historiography is historical research so that this research can be completed. Hail research shows the development of the Alang Bangkeh Pauh V tribe on its journey for 37 years in order to be able to promote Silat Pauh. Alang Bangkeh martial arts schools progressed in the period 2000 to 2018 by winning many Silat championships shaded by IPSI organizations such as the arena of penant baganti the traditional Minangkabau Martial arts festival. But a time goes by, Alang Bangkeh school has established a management system from the university leadership, secretaries,treasurers, and other members. Although the Alang Bangkeh martial arts school already has auniversiy, the management system has not yetrun well. In terms of facilities and infrastructure is very limited in the Alang Bangkeh martial arts college.This has no impacton the achievements of the Alang Bangkeh martial arts insitution in popularizing the traditional Minangkabau martial arts.